EXPERIMENTAL STUDY OF IMPLANTATION OF DIFFERENT KINDS OF MESHES INTO THE ABDOMINAL WALL WITH THEIR INTRAABDOMINAL PLACEMENT - Krуvopustov, Mykola; Tarasiuk, Tetiana; Ioffe, Oleksandr (The Ukrainian Scientific Medical Youth Journal, 2020)
The article discusses the features of implantation of various types of composite meshes into the anterior abdominal wall. The main purpose of the study was to assess the speed and reliability of fixation of the mesh implant to the parietal peritoneum, its integration into the abdominal wall and the severity of the development of adhesions in the abdominal cavity against the background of intra-abdominal implant placement. The relevance of the study lies in the growth in the percentage of laparoscopic hernioplasty with intra-abdominal mesh placement in medical practice. At the same time, data on the rate of implantation of various types of meshes into the anterior abdominal wall are limited. This leads to a discussion about the choice of the optimal mesh type for its intra-abdominal placement. The research technique consisted in studying the degree of implantation of three types of polypropylene composite meshes into the anterior abdominal wall in an experiment on 27 white Wistar rats. A 2 x 2 cm mesh was fixed to the parietal peritoneum of the anterior abdominal wall intra-abdominally. We used composite polypropylene meshes with various types of structure and outer coating: group I - one-sided anti-adhesive coating with oxidized regenerated cellulose (n = 9), group II - double-sided anti-adhesive coating of polylecapron-25 (n = 9), group III - one-sided anti-adhesive coating with fatty acids Omega-3 (n = 9). The article presents the results of a chronic experiment assessing the state of mesh implantation on days 14, 30 and 90. An analysis of the severity of the adhesive process between the antiadhesive coating of the implant and the visceral peritoneum was carried out. There were no statistically significant differences between the groups in the macroscopic assessment of the adhesive process on days 14, 30, 90 of observation (p> 0.05). Histological examination of the “anterior abdominal wall - implant complex” did not confirm statistically significant differences in the strength of mesh fixation in groups I and II to the anterior abdominal wall (p = 0.387) in total for all observation periods, however, on day 30, the formation of a two-layer capsule and seromas was revealed in group II. The formation of neoperitoneum was observed only when using a mesh with an anti-adhesive one-sided coating of oxidized regenerated cellulose on day 90 of observation. The study empirically confirms and theoretically proves that the absence of an anti-adhesive coating in the zone of contact with the parietal peritoneum provides a short time for mesh implantation into the anterior abdominal wall and mesothelium formation. The results of the study can be useful when choosing the type of composite polypropylene mesh in patients with hernias of the anterior abdominal wall, for whom the method of surgical treatment is chosen - laparoscopic prosthetic hernioplasty with intra-abdominal implant placement.